Injuries among elite snowboarders (FIS Snowboard World Cup) - Torjussen, J.; Bahr, R. (British Journal of Sports Medicine, 2006)
Background: Although snowboarding is already established as an Olympic sport, it is still a developing sport, with new disciplines, more demanding snow installations, and spectacular tricks. A recent study on subjects at Norwegian national elite level showed that injury risk is high and that injuries among competitive snowboarders differ from those seen in recreational snowboarders, with fewer wrist injuries and more knee and back injuries.